2018
DOI: 10.1002/2017gl076828
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Extreme Time‐Integrated Geomagnetic Activity

Abstract: A statistical analysis of the time‐integrated Dst index is performed over 1958–2007. The tail of the probability distribution of extreme time‐integrated Dst events, which occur during strong geomagnetic storms, can be precisely fitted by a power law function with upper cutoff, apparently not exceeded even by the 1859 Carrington event. This time‐integrated Dst is expected to be a reasonable proxy for maximum densities of MeV electrons in the heart of the outer radiation belt, which are known to pose a serious t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 99 publications
(275 reference statements)
2
30
0
Order By: Relevance
“…In addition, many of these works mainly considered the geostationary orbit (i.e., the outer edge of the radiation belt) or only examined several years of electron flux data from the Van Allen Probes with a relatively long time step, ∼5–9 hr (Moya et al, ; Murphy et al, ; Tang et al, ; Turner, O'Brien, et al, ; Zhao, Baker, Jaynes, et al, ). Furthermore, recent studies have shown that the most significant correlations with electron flux increases are found when considering geomagnetic indices ( K p , D s t , or ULF wave index) integrated in time over at least 1 day (during the considered storm or periods of sustained substorms), instead of their hourly or peak value, suggesting the presence of cumulative effects (Borovsky, ; Mourenas et al, ; Simms et al, ). This kind of correlation between a progressive flux increase and an extended period of geomagnetic activity could be easily identified through a superposed epoch analysis over hundreds of events.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many of these works mainly considered the geostationary orbit (i.e., the outer edge of the radiation belt) or only examined several years of electron flux data from the Van Allen Probes with a relatively long time step, ∼5–9 hr (Moya et al, ; Murphy et al, ; Tang et al, ; Turner, O'Brien, et al, ; Zhao, Baker, Jaynes, et al, ). Furthermore, recent studies have shown that the most significant correlations with electron flux increases are found when considering geomagnetic indices ( K p , D s t , or ULF wave index) integrated in time over at least 1 day (during the considered storm or periods of sustained substorms), instead of their hourly or peak value, suggesting the presence of cumulative effects (Borovsky, ; Mourenas et al, ; Simms et al, ). This kind of correlation between a progressive flux increase and an extended period of geomagnetic activity could be easily identified through a superposed epoch analysis over hundreds of events.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, we keep over each sliding window the minimum value of Dst and the maximum values of ap, AE, and AL, calculating also IntDst as the time‐integrated false|Dstfalse| when Dst<70 nT (Mourenas et al, ), Intfalse(apfalse) as the time‐integrated ap when ap15, and IntAE and IntAL as time‐integrated AE and false|ALfalse| over periods where ap15, as in Mourenas et al (). However, we do not require here geomagnetic activity to remain continuously strong over the time integration window, because when considering significant time‐integrated IntDst or Intfalse(apfalse) values >1,500 nT ·hr, the relative weight of one important continuous event generally largely dominates over the 10 days of the integration window.…”
Section: Correlations Between Sample Entropy Of Geomagnetic Indices Amentioning
confidence: 99%
“…To check possible differences between entropy variations during quiet or moderately disturbed periods and entropy variations during strong disturbances, best least‐squares fits have also been calculated separately during low and high geomagnetic activity (see dashed and dotted blue curves in Figure ), using approximate thresholds of high activity false|Minfalse(Dstfalse)false|>100 nT, IntDst> 2,000 nT ·hr, Maxfalse(apfalse)>50 nT, Intfalse(apfalse)>1,500 nT ·hr from previous studies (Mourenas et al, , ; Tsurutani et al, , ), such that highly active periods represent 10% to 20% of the data points. The results in Figure show that the best global fits (obtained by considering all data points) generally remain close to the best fits obtained during moderately disturbed periods (comprising 90% of the data points).…”
Section: Correlations Between Sample Entropy Of Geomagnetic Indices Amentioning
confidence: 99%
See 2 more Smart Citations